Journal PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN BERKUNJUNG SERTA DAMPAKNYA TERHADAP KEPUASAN WISATAWAN DI MUSEUM PURBAKALA DAYU KABUPATEN KARANGANYAR: PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN BERKUNJUNG SERTA DAMPAKNYA TERHADAP KEPUASAN WISATAWAN DI MUSEUM PURBAKALA DAYU KABUPATEN KARANGANYAR - Erwin Purbosaputro Erwin (Sekolah Tinggi Pariwisata Sahid Surakarta, 2023)
There are many motivational factors for tourists to be interested and visit a tourist attraction or a tourist destination, these factors consist of various variables. In these conditions a product, promotion, decision of a visit is an important factor that will produce or are expected to meet the tourist's decision. This study aims to determine the effect of products and promotion of visiting decisions and their impact on tourist satisfaction at the Dayu Archaeological Museum in Karanganyar Regency. The research was conducted with quantitative methods. A sample of 95 tourists from the Dayu Archaeological Museum were taken by accidental sampling. Data collection techniques using questionnaires and data were tested and analized with path analysis and one intervening variable with SPSS. Based on the results of the analysis of research data it can be concluded that: (1) Products have a positive and significant effect on visiting decisions and their impact on tourist satisfaction, (2) Promotion has a positive and significant effect on visiting decisions and their impact on tourist satisfaction, (3) Visiting decisions have a positive effect and significant to tourist satisfaction.